Small-scale benthic faunal activities may lead to large-scale morphological change- A model based assessment - Arlinghaus, Peter; Zhang, Wenyan; Schrum, Corinna (Frontiers in Marine Science, 2022)
A novel 3-dimensional numerical model resolving dynamic interactions between environmental drivers and benthic fauna was applied to an idealized domain as analogous to typical tidal embayments. The aim is to derive insights into the role of benthic fauna in guiding long-term (decadal to centennial) coastal morphological evolution at a system scale. Three major functions by benthic fauna on sediment dynamics, namely bio-destabilization, bio-deposition and bio-stabilization, were incorporated. Results indicate that each of the three functions is able to guide a unique and profound long-term change of the embayment morphology. Bioturbation-induced sediment mixing and bio-destabilization may result in net sediment export out of the embayment, whilst bio-deposition and bio-stabilization tend to alter the embayment toward a net sediment import environment. Benthic fauna is able to modify large-scale hydro-morphology toward a state favorable for living. A combined effect of the three functions is not just a simple neutralization of the opposing impacts between sediment stabilization and destabilization. Rather, it leads to a unique response of the embayment morphology due to interactions between different benthic functional groups. Comparison with a real tidal embayment (Jade Bay from the Wadden Sea) justified a general validity of the model results in terms of statistics in both morphology and benthic fauna, and suggested an equal importance of interactions between benthic fauna and bed morphology and between different benthic functional groups in guiding morphological development of complex coastal systems.